What do 25 million records of small businesses say about the effects of the PPP? - Gustavo Joaquim; J. Christina Wang (Federal Reserve Bank of Boston, 2022)
We utilize Dun & Bradstreet data on firms' financial condition to examine the allocation of Paycheck Protection Program (PPP) loans and their impact. Three main findings emerge. First, firms in better financial condition prior to the COVID outbreak were advantaged in the allocation of PPP loans. Second, firms' financial condition improved significantly and persistently after receiving a loan, and this effect was more pronounced among the smaller and less financially sound firms. Third, we demonstrate empirically that the heterogeneity in firms' financial condition must be accounted for to correctly identify and estimate the overall effect of the PPP.
Keywords: H81; G28; J21; E24; 330; Paycheck Protection Program; small business lending; financial frictions